Impact of carbon trading policy on corporate capital structure: Empirical evidence from China - Zhang, Zhaolong; Liao, Jing; Li, Hanlin; Pan, Jiaqi (Frontiers in Environmental Science, 2023)
Nowadays, the impact of environmental regulation on firm behavior has been a hot topic worth studying. In this paper, we examine how the environmental regulation and transition risks associated with climate change affect corporate capital structure, which is currently being studied less, but is practical. China is a good example for our study. The Chinese government has taken the lead in proposing a carbon trading market policy to address the negative impact of excessive carbon emissions on global climate change. This policy has been implemented since year 2011 and has had a profound impact on the economic development and structure. Taking listed companies in China for sample, this study uses a Difference-in-Difference(DID) model to examine the impact of carbon trading policy on corporate capital structure. The result shows that, carbon trading policy will significantly reduce corporate debt ratio, and it still holds when the instrumental variables approach is used to deal with endogeneity and robustness tests are conducted. This study also shows that the negative effect of carbon trading market policy on corporate capital structure is mainly influenced by the internal capital demand and the external capital supply. In addition, the reduction effect of carbon trading market policy on corporate debt ratio is more significant among firms with higher government subsidies and the state-owned ones. The findings suggest that the financial decision of firms will change under the implementation of carbon trading market policy in response to the policy-induced shocks of elevated corporate risk.